Physicochemical and Fungal Analysis of a Hydrocarbon-Polluted Soil at Amadi-Ama Creek of Bonny River Port Harcourt, Rivers State, Nigeria - Iheanacho, Chinedu Christian; Nkwocha, Ikenna Light; Mgbede, Timothy; Abah, Moses Adondua; Osagie, Asuelimen Steve; Nonye, Eze Constance; Oyibo, Okpanachi Nuhu; Samuel, Woyengibarakemi Ann; Akpan, Rose Aniekan; Umezurike, Kingsley Chimuanya; Marvis, Alajemba Chinonso; Idris, Nancy (Asian Journal of Science, Technology, Engineering, and Art, 2024)
Numerous hydrocarbon-utilizing fungal species have been implicated with the ability to utilize/degrade hydrocarbon as carbon source, which indicate their potential for environmental cleanup in hydrocarbon-contaminated sites. In this study, five (5) indigenous fungal species were isolated from a petroleum-hydrocarbon polluted soil at Amadi-ama Creek, Bonny river shoreline, Port Harcourt, Rivers State. These fungal species may have high potential to biodegrade petroleum hydrocarbon pollutants. Samples were collected randomly from the hydrocarbon impacted soil at Amadi-ama Creek, Bonny river shoreline. Sabouraud’s Dextrose Agar (SDA) and Czapek Agar were used as growth media. Samples were examined to assess the physical and chemical characteristics such as conductivity, pH, temperature, nitrate, iron, copper, zinc, chromium, phosphate, sulphate, total hydrocarbon content, total petroleum hydrocarbon, and polycyclic aromatic hydrocarbon. These parameters are known to influence the occurrence, diversity and distribution of microorganisms in an ecological niche. Soil pH showed to be acidic (6.21), result also showed that Total hydrocarbon content, Total petroleum hydrocarbon and Polycyclic aromatic hydrocarbon values were at 306.55mg/kg, 112.134mg/kg, 44.227mg/kg respectively establishing the incidence of hydrocarbon pollution. Electrical conductivity and Temperature were at 1250 Us/cm, and 29.580C respectively while Nitrate, Phosphate, Sulphate, Iron, Copper, Zinc, and Chromium values were at 1.228mg/kg, 0.751mg/kg, 20.214mg/kg, 18.431mg/kg, 0.113mg/kg, 0.121mg/kg, and 0.042mg/kg respectively. Monitoring of the soil quality established the incidence of hydrocarbon pollution as well the incidence of anthropogenic influence on the soil putting into cognizance human activities at the shoreline. Morphological identification of obtained fungal species led to their assignment into four (4) genera and five (5) species; Aspergillus niger (28%), Aspergillus flavus (22%), Cladosporium herbarum (20%), Penicillium notatum (17%), Fusarium spp (11%). The predominance of Aspergillus isolates (28% and 22%) in this study could be a pointer to their potential to utilize hydrocarbon as their sole source of nutrient. The isolation of these indigenous fungal species could serve as a baseline study on which further analysis such as hydrocarbon degradation screening test could determine their individual hydrocarbon degradation potentials and subsequent consideration as hydrocarbon degrading microbes in subsequent bioremediation study.